Non-Composted Chinaberry (Melia azedarach L.) Sawdust Mixtures as Growth Medium for Okra (Abelmoschus esculentus (L.) Moench) - Muhammad Yasin; Hassan Noorani; Farhan Anwar; Manahil Siddiqui; Muhammad Ehsan Safdar; Christian Andreasen (Agriculture, 2022)
Sawdust as a soilless growth substrate for plants is becoming popular in greenhouse production. However, fresh sawdust often requires time for decomposition before it is ready for use as a growth substrate. We studied whether amendments of banana peels (as a source of potassium), eggshells (as a source of calcium), and urea (as a source of nitrogen) in non-composted fresh chinaberry (Melia azedarach) sawdust could enhance its potential as a growth medium. In two pot experiments, the growth of okra (Abelmoschus esculentus (L.) Moench) was evaluated using mixtures of non-composted M. azedarach sawdust. The treatments were: (T1) 100% soil (control) (vol/vol); (T2) 100% M. azedarach sawdust (vol/vol); (T3) 80% M. azedarach sawdust +20% banana peel (vol/vol); (T4) 60% M. azedarach sawdust +20% banana peel +20% eggshell (vol/vol); and (T5) 60% M. azedarach sawdust +20% banana peel +20% eggshell (vol/vol) +91 kg N ha−1 (urea). There was no significant difference between the treatments regarding seed germination and okra emergence, but leaf area, chlorophyll content index, plant biomass, number of pods per plant−1, fresh pods, and dry weight were significantly lower in pots with fresh sawdust mixtures. Organic amendments of banana peels and eggshells improved the sawdust substrate. Adding a further 91 kg N hectare−1 improved the growth but was insufficient to produce the same yield of okra as in non-fertilized sandy clay loam soil. We cannot exclude that non-composted M. azedarach sawdust may be a potential growth substrate for okra, but the amendments added were not enough to obtain the same yields as when okra was grown in soil.